Agrobacterium–mediated transformation of cry3ca1 gene into kb1 sweet potato cultivar - Lan, Vu Thi; Ngoc, Pham Bich; Ha, Chu Hoang; Binh, Le Tran (Academia Journal of Biology, 2018)
Sweet potato Ipomoea batatas (L.) Lam is an important food crop in the world as well as in Vietnam. Despite its many benefits, the production of sweet potato is restricted in many areas of the world by diseases, weed, and, particularly, pests. As an alternative, genetic transformation provides the means for complementing conventional breeding to improve sweet potato to resistant to pest. In this study, shoot tip explants of KB1 sweet potato variety were infected with A. tumefaciens C58 carying pBI101/cry3Ca1 con-struct. The selection were occured on callus producing medium (SM) containing 0.5 g/L picloram, 50 mg/L kanamycin and 500 mg/L cefotaxime. Survival embryogenic calli were then transferred to embryo producing medium (EG2) supplemented with 1.0 mg/L ABA and 1.0 mg/L GA3 after 2–3 weeks. Putative transgenic shoots regenerated on medium (RM) adding 0.5 mg/L kinetin and 1.0 mg/L BAP were rooted on root producing medium (RR). The tentative transgenic lines were proved positively by PCR and finalized by Southern hybridization, and biotest in laboratory. Conclusionly, we obtained 62 tentative transgenic sweet potato lines resistant to kanamycin. Among these lines, five putative transgenic lines were proved positively by Southern hybridization and have one copies of the cry3Ca1 gene. Two of them have the lower degree of infestation by sweet potato weevil (Cylas formicarius) than that of untransformed lines